Accessing specialist support to stop smoking in pregnancy: A qualitative study exploring engagement with UK‐based stop smoking services. Issue 3 (1st December 2021) - Griffiths, Sarah Ellen; Naughton, Felix; Brown, Katherine E.
Abstract : Objectives: Specialist stop smoking services can be effective for supporting women with smoking cessation during pregnancy, but uptake of these services is low. A novel theoretical approach was used for this research, aiming to identify barriers to and facilitators of engaging with specialist smoking cessation support using the Theoretical Domains Framework (TDF). Methods: Semi‐structured interviews and a focus group ( n = 28) were carried out with pregnant women who smoke/recently quit smoking, midwives and Stop Smoking in Pregnancy advisors from two local authority commissioned services in the UK. Inductive thematic analysis was used to code interview transcripts and deductive thematic analysis used to match emerging themes to TDF domains. Results: Themes corresponded to seven domains of the TDF: Knowledge: Knowledge of available services for pregnant smokers; Environmental context and resources: Uptake of referral to cessation services by pregnant smokers; Social Influences: Smoking norms and role of others on addressing smoking in pregnancy; Beliefs about Capabilities: Confidence in delivering and accepting pregnancy smoking cessation support; Beliefs about Consequences : Beliefs about risks of smoking in pregnancy and role of cessation services; Intentions : Intentions to quit smoking during pregnancy; Emotions: Fear of judgement from healthcare professionals for smoking in pregnancy. Conclusions: These novel findings help to specify factors associated with pregnant women's engagement, which are useful for underpinning service specification and design by public health commissioners and service providers. Addressing these factors could help to increase uptake of cessation services and reduce rates of smoking in pregnancy.